Considerations Regarding the Model of Polish Preparatory Proceedings - Bojanowski, Tomasz (Central European Academy Law Review, 2023)
The subject of this article is the analysis of selected issues of the Polish model of preparatory proceedings. The author begins his considerations by highlighting historical and model issues, whereafter he discusses the goals of preparatory proceedings resulting from the Code of Criminal Procedure 1997. The next segment analysed is the forms and phases of preparatory proceedings. Further on, the article discusses the prosecutor‘s supervision of preparatory proceedings and the role of the judicial factor in this phase of preparatory proceedings. The last substantive subsection deals with the options for the termination of preparatory proceedings. It concludes with a final assessment of the model—divided into its advantages and disadvantages. In addition, the author derives de lege fereneda conclusions, which would contribute to the improvement of the current model of Polish preparatory proceedings.